Stability analysis of a non-minimum phase Electro-Hydraulic Servo System (EHSS) and identification of parametric uncertainty - Ahmed, Mazid Ishtique (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Master of Science in Electrical and Electronic Engineering, 2021.